The Influence of Reward and Punishment on Employee Discipline in Public Sector Organizations: A Systematic Literature Review - Kahono, Tri Kahono; Utomo, E Mohammad Nur; Azis, Muh Irfandy; Shalahuddin, S. (Manunggal Halim Jaya, 2026)
This study aims to systematically examine the literature on the effects of reward and punishment on employee discipline in public organizations. It is motivated by the phenomenon of low employee discipline, which impacts declining performance and the effectiveness of public services. The study employs a systematic literature review conducted in November 2025, following the PRISMA guidelines, and searches Google Scholar, Portal Garuda, Semantic Scholar, and DOAJ for articles. The initial screening yielded 968 articles from Google Scholar, 7 from Portal Garuda, 12 from Semantic Scholar, and 10 from DOAJ. The articles were filtered using inclusion criteria, namely, peer-reviewed articles, full-text in Indonesian, research articles, and publications from 2020 to 2025, while non-peer-reviewed articles, non–full-text articles, non-Indonesian articles, non-research articles, publications outside the specified years, studies not addressing reward and punishment in relation to employee discipline, or those with low methodological quality were excluded. The results show five main effects. First, rewards have a positive, significant effect on employee discipline and performance. Second, punishment also has a positive and significant effect when applied fairly, as it can correct behavior and enhance employee compliance. Third, rewards are more effective than punishments in creating behavioral change. Fourth, work discipline acts as an intervening variable, strengthening the effects of rewards and punishments on performance. Fifth, the proportional and fair application of rewards and punishments can increase motivation, compliance, and employee performance in public organizations.